Improving hierarchical porous structure of carbon aerogels for more efficient ion transport for supercapacitors with commercial level mass loading. (10th November 2019) - Wang, Dong; Fan, Wei; Yuan, Shijia; Liu, Tianxi
Abstract: Designing porous structure and surface properties of carbon electrodes is the key premise for efficient electron/ion transfer, which is crucial for improving electrochemical performance of supercapacitors in practical applications. Herein, N-doped activated carbon aerogel (NACA) with hierarchical porous structure and N, O-rich functionalities has been prepared from polyimide gel by activation and carbonization process. The NACA exhibits a high surface area of 1410 m 2 g −1 with hierarchical porous structures, with both high micropore volume (0.481 cc g −1 ) and mesopore volume (0.566 cc g −1 ) as well as high heteroatom content, which is favorable for charge storage, ion transfer and electrolyte penetration. As a result, the NACA2-11 can deliver a high capacitance of 386 F g −1 at 1 A g −1 in a three-electrode system and outstanding rate performance with the capacitance retaining 150 F g −1 at 100 A g −1 in aqueous electrolyte. Furthermore, the practical two-electrode device exhibits a high areal specific capacitance of 1584 mF cm −2 under the commercial level mass loading of 10 mg cm −2, and it stays a good cycling stability of 93% capacitance retention after 10000 cycles at 5 A g −1 . This study paves the way for improving electrochemical performance of carbon-based supercapacitor under high mass loadings. Graphical abstract: N-doped activated carbon aerogel (NACA) with hierarchical porous structure and N, O-rich functionalities exhibits good capacitive behavior under the commercial level mass loading.Image 1 Highlights: NACA with hierarchical porous structure and N, O-rich functionalities has been prepared. NACA exhibits a high surface area of 1410 m 2 g −1 with both high micropore and mesopore volume. NACA exhibits outstanding rate performance with the capacitance retaining 150 F g −1 at 100 A g −1 . NACA facilitates ion transport for supercapacitors under commercial level mass loading.